Numerical Solution of Linear Volterra Integral Equation of the Second Kind with Delay Using Lagrange Polynomials - Dhari, Iman A.; Mustafa, Muna M. (Iraqi Journal of Science, 2024)
In this study, the linear Volterra integral problem of the second kind will be treated with delay using a Lagrange polynomial. The Volterra integral problem is solved numerically using the chosen technique to obtain the best approximation. Additionally, the test examples are provided to demonstrate, through comparison with other methods’ outcomes, the great degree of accuracy of the approximative solutions. Moreover, To verify the accuracy of the calculations that is used in these test examples, the absolute error is used to compare it to the exact solution. For this method, the program is written by MATLAB R2018a language.